2012
DOI: 10.1136/medethics-2011-100428
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of neonatal professionals towards end-of-life decision-making for dying infants in Taiwan

Abstract: The purposes of research were to describe the neonatal clinicians' personal views and attitudes on neonatal ethical decision-making, to identify factors that might affect these attitudes and to compare the attitudes between neonatal physicians and neonatal nurses in Taiwan. Research was a cross-sectional design and a questionnaire was used to reach different research purposes. A convenient sample was used to recruit 24 physicians and 80 neonatal nurses from four neonatal intensive care units in Taiwan. Most pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 29 publications
3
26
1
3
Order By: Relevance
“…However, they disagreed with administering drugs for the purpose of ending life, withholding neonatal intensive care (i.e., resuscitation at birth or mechanical ventilation), and withdrawing mechanical ventilation. In other words, the respondents agreed more with using conservative, rather than active, interventions in relation to end-of-life decision making about dying neonates; these results are similar to the findings obtained from studies conducted in other Asian countries 9,11) . In contrast, our results differ from those obtained from studies conducted in European countries, where many doctors agreed with using active interventions, such as withdrawal of mechanical ventilation 8,[12][13][14][15] .…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…However, they disagreed with administering drugs for the purpose of ending life, withholding neonatal intensive care (i.e., resuscitation at birth or mechanical ventilation), and withdrawing mechanical ventilation. In other words, the respondents agreed more with using conservative, rather than active, interventions in relation to end-of-life decision making about dying neonates; these results are similar to the findings obtained from studies conducted in other Asian countries 9,11) . In contrast, our results differ from those obtained from studies conducted in European countries, where many doctors agreed with using active interventions, such as withdrawal of mechanical ventilation 8,[12][13][14][15] .…”
Section: Discussionsupporting
confidence: 82%
“…Although the respondents replied that it was necessary to suggest to parents of dying neonates that they sign DNR orders (62.7%), the agreement rate was much lower than that observed in another study (86.5%) 9) . Moreover, in this study, we also observed a clearer tendency toward the respondents finding it difficult or wanting to refrain from suggesting DNR orders or obtaining consent from families in person 9) .…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations